Iron-doped graphite carbon nitride catalysts, methods of making and using the same
Patent Information
- Application Number
- CN202611369178.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]高级氧化工艺依靠活性自由基破坏污染物分子结构,其中太阳光活化高碘酸盐体系对 6PPD-Q 具备优异降解能力,但该工艺抗水体基质干扰性能差:Chen L等人的研究显示,该催化体系对 1 mg/L 浓度的 6PPD-Q 纯水体系处理 10 min 即可实现 90% 去除率,而水体中引入氯离子、腐殖酸等天然干扰物质后,同等条件下污染物去除率跌至 60%,共存杂质会严重削弱体系降解效率(Chen L, Hu J, Borthwick A G, et al. Solar-light-activated periodate for degradation and detoxification of highly toxic 6PPD-quinone at environmental levels[J]. Nature Water, 2024, 2: 453-463.);此外常规紫外光氧化工艺处理效率偏低,单独紫外光照射 2 h 仅能去除水中 13.3% 的 6PPD-Q(YuW, Tang S, Wong J W C, et al. Degradation and detoxification of 6PPD-quinonein water by ultraviolet-activated peroxymonosulfate: Mechanisms, byproducts,and impact on sediment microbial community[J]. Water Research, 2024, 263:122210.),整体处理周期过长,难以快速处置突发污染
[0024] 1. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies of the present invention significantly improves the generation efficiency of active species through photo-PMS synergistic activation. For a pollutant solution with an initial concentration of 1000 μg/L of 6PPD-Q, the pollutant removal rate can reach 100% within 5 minutes under visible light irradiation, which is far superior to pure graphitic carbon nitride or single PMS system.
Smart Images

Figure CN122912900A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, specifically relating to an iron-doped graphite carbon nitride catalyst, its preparation method, and its application. Background Technology
[0002] N-(1,3-Dimethylbutyl)-N'-phenyl-p-phenylenediamine quinone (6PPD-Q) is a rubber antioxidant and a key byproduct of the formation of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) through environmental transformation processes such as ozone oxidation and solar radiation. As a typical emerging aquatic pollutant, it is widely present in various aquatic media worldwide and has become a significant threat to the safety of aquatic ecosystems. Furthermore, 6PPD-Q can accumulate in fish, crustaceans, and other organisms through the food chain and bioaccumulation, and its presence has been detected in human urine, whole blood, and cerebrospinal fluid, potentially posing health risks to the human cardiovascular and nervous systems. Therefore, there is an urgent need to develop efficient 6PPD-Q removal technologies.
[0003] Currently, the main technologies for removing 6PPD-Q from water bodies focus on advanced oxidation processes (AOPs) and biodegradation, with significant differences in the principles, effectiveness, and application scenarios of these technologies.
[0004] Advanced oxidation processes rely on reactive free radicals to destroy the molecular structure of pollutants. Among them, the solar-activated periodate system has excellent degradation ability for 6PPD-Q. However, this process has poor resistance to interference from the water matrix. The study by Chen L et al. showed that the catalytic system can achieve a 90% removal rate of 1 mg / L 6PPD-Q in pure water after 10 min of treatment. However, after introducing natural interfering substances such as chloride ions and humic acid into the water, the pollutant removal rate drops to 60% under the same conditions. Coexisting impurities will seriously weaken the degradation efficiency of the system (Chen L, Hu J, Borthwick AG, et al. Solar-light-activated periodate for degradation and detoxification of highly toxic 6PPD-quinone at environmental levels[J]. Nature Water, 2024, 2: 453-463.). In addition, the conventional ultraviolet oxidation process has low treatment efficiency. Only 13.3% of 6PPD-Q in water can be removed by 2 h of ultraviolet irradiation alone (YuW, Tang S, Wong JWC, et al.). Degradation and detoxification of 6PPD-quinonein water by ultraviolet-activated peroxymonosulfate: Mechanisms, byproducts, and impact on sediment microbial community[J]. Water Research, 2024, 263:122210.), the overall treatment cycle is too long, making it difficult to quickly deal with sudden pollution.
[0005] Microbial degradation technology utilizes the enzymatic reaction of fungi and sedimentary microorganisms to convert 6PPD-Q. However, this type of process is highly limited by water temperature and pollution load. In water bodies with low temperature or high pollutant concentration, the activity of microorganisms will be greatly reduced, the degradation rate will be slow, and it will not be able to meet the needs of emergency pollution control.
[0006] Advanced oxidation processes have weak resistance to interference, and some oxidation pathways can generate ecotoxic intermediate byproducts; microbial degradation systems have slow reaction rates. None of the existing technologies can simultaneously meet the three core requirements of treatment efficiency, water adaptability, and operating costs.
[0007] Therefore, developing 6PPD-Q removal technology that combines high efficiency, water quality stability, economy, and environmental friendliness is of great significance for ensuring water environmental quality and water ecological security. Summary of the Invention
[0008] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for preparing an iron-doped graphitic carbon nitride catalyst with nitrogen vacancies.
[0009] Another object of the present invention is to provide an iron-doped graphitic carbon nitride catalyst with nitrogen vacancies obtained by the above preparation method.
[0010] Another object of the present invention is to provide the application of the above-mentioned iron-doped graphitic carbon nitride catalyst with nitrogen vacancies in the degradation of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine quinone (6PPD-Q).
[0011] The objective of this invention is achieved through the following technical solution.
[0012] A catalyst comprising iron-doped graphitic carbon nitride having nitrogen vacancies.
[0013] In the above technical solution, the g value of the paramagnetic center generated by nitrogen vacancies is 2.0030~2.0038.
[0014] A method for preparing an iron-doped graphitic carbon nitride catalyst with nitrogen vacancies includes the following steps:
[0015] Step 1: Mix dicyandiamide, water and iron source, stir at 80~100℃ until water evaporates completely, grind, keep the ground powder at 540~560℃ for 3.5~4h, cool to room temperature to obtain iron-doped graphitic carbon nitride (Fe / CN), wherein the mass fraction of dicyandiamide to the molar fraction of iron in the iron source is 2:(0.25~1), the mass fraction is in g, and the molar fraction is in mmol;
[0016] In step 1, the preferred ratio of the mass fraction of dicyandiamide to the molar fraction of iron in the iron source is 2:(0.4~0.6), where the mass fraction is in g and the molar fraction is in mmol.
[0017] In step 1, the iron source is ferric chloride hexahydrate (FeCl3·6H2O).
[0018] In step 1, the ratio of the mass fraction of dicyandiamide to the volume fraction of water is 2:(20~30), where the mass fraction is in g and the volume fraction is in mL.
[0019] Step 2: Under a nitrogen or inert gas atmosphere, iron-doped graphitic carbon nitride is heated at 600~620℃ for 3.5~4h and then cooled to room temperature to obtain an iron-doped graphitic carbon nitride catalyst (Fe / CN-V) with nitrogen vacancies.
[0020] The above-mentioned iron-doped graphitic carbon nitride catalysts with nitrogen vacancies are used in the degradation of pollutants.
[0021] In the above technical solution, the pollutant is at least one of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine quinone (6PPD-Q), tetracycline (TC), and sulfamethoxazole (SMX).
[0022] In the above technical solution, an iron-doped graphitic carbon nitride catalyst with nitrogen vacancies activates PMS under light irradiation to generate singlet oxygen (…). 1 O2).
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies of the present invention significantly improves the generation efficiency of active species through photo-PMS synergistic activation. For a pollutant solution with an initial concentration of 1000 μg / L of 6PPD-Q, the pollutant removal rate can reach 100% within 5 minutes under visible light irradiation, which is far superior to pure graphitic carbon nitride or single PMS system.
[0025] 2. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies of the present invention has a wide photoresponse range. Fe doping broadens the light absorption boundary from around 460nm in pure graphitic carbon nitride to 550~600nm, which can effectively utilize natural sunlight without relying on ultraviolet light sources, reduce energy consumption, and is suitable for actual water treatment scenarios.
[0026] 3. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies of the present invention has strong anti-interference ability and stable degradation performance in different coexisting ions and a wide pH range, and can be adapted to a variety of complex aquatic environments.
[0027] 4. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies of the present invention has high stability, good structural integrity and low metal ion leakage during degradation.
[0028] 5. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies of the present invention can achieve efficient photo-PMS synergistic activation for the removal of 6PPD-Q. 1 The generation of O2 active species.
[0029] This invention utilizes the synergistic effect of iron doping modification and nitrogen vacancy defect construction to construct highly efficient photo-PMS synergistic activation sites, promoting the activity of species (…). 1 The generation of O2 improves the selective degradation and toxicity reduction efficiency of 6PPD-Q. Attached Figure Description
[0030] Figure 1 The image shows the microstructure of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3, where a is a TEM image and b is an aberration-corrected HAADF-STEM image.
[0031] Figure 2 The elemental mapping diagram is shown for the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3.
[0032] Figure 3 X-ray diffraction patterns of the graphitic carbon nitride prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3.
[0033] Figure 4 Fourier transform infrared spectra of the graphitic carbon nitride prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 1, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Examples 3-4.
[0034] Figure 5 The UV-Vis diffuse reflectance spectra of the graphitic carbon nitride prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3.
[0035] Figure 6 The photoluminescence spectra of the graphitic carbon nitride prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 are shown.
[0036] Figure 7 The test results are from Experiment 1 in Test Example 1;
[0037] Figure 8 The test results are from Experiment 2 in Test Example 1;
[0038] Figure 9 The test results are from Experiment 3 in Test Example 1;
[0039] Figure 10 The test results are from Experiment 4 in Test Example 1;
[0040] Figure 11 The test results are for test example 2;
[0041] Figure 12 The test results are for test example 3;
[0042] Figure 13 The test results are for test example 4;
[0043] Figure 14 The test results are for test example 5;
[0044] Figure 15 The test results are for test example 6;
[0045] Figure 16 Captured in test case 7 1 Test results of the O2 experiment;
[0046] Figure 17 Captured in test case 7 1 In the O2 experiment, the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 was used as the catalyst, and the results and capture... 1 Results of the O2 control experiment;
[0047] Figure 18 The test results are for the hole trapping experiment in Test Example 7;
[0048] Figure 19 The results are for test example 8. Detailed Implementation
[0049] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0050] The pharmaceutical products, molecular formulas, purities, and manufacturers of purchase involved in the following examples and comparative examples are as follows:
[0051]
[0052] The instruments, models, and manufacturers involved in the following embodiments are as follows:
[0053]
[0054] In the following examples and comparative examples, the water used is ultrapure water.
[0055] The xenon lamp has a power of 300 W and a built-in 420 nm filter.
[0056] Examples 1-4
[0057] A method for preparing an iron-doped graphitic carbon nitride catalyst with nitrogen vacancies includes the following steps:
[0058] Step 1: Mix dicyandiamide, water, and iron source (ferric chloride hexahydrate) at 80°C and stir at 80°C for 1.5 hours until the water is completely evaporated. Grind manually for 10 minutes. Heat the resulting powder to 550°C (heating rate to 550°C is 2°C / min) and keep it at 550°C for 4 hours to remove residual moisture. Cool to room temperature to obtain iron-doped graphitic carbon nitride (Fe / CN). The mass ratio of dicyandiamide to the molar ratio of iron in the iron source is X, where mass is expressed in g and molar ratio in mmol. The volume ratio of dicyandiamide to water is 2:20, where mass is expressed in g and volume ratio in mL.
[0059] Step 2: Under an argon atmosphere (argon flow rate of 20 mL / min), iron-doped graphitic carbon nitride was kept at 620℃ for 4 h and then cooled to room temperature to obtain an iron-doped graphitic carbon nitride catalyst (Fe / CN-V) with nitrogen vacancies.
[0060] The values of X are shown in Table 1.
[0061] Table 1
[0062]
[0063] Comparative Example 1
[0064] A method for preparing graphitic carbon nitride (CN) includes: holding dicyandiamide (powder) at 550 °C (heating rate to 550 °C is 2 °C / min) for 4 h in an argon atmosphere (argon flow rate is 20 mL / min), and cooling to room temperature to obtain graphitic carbon nitride (CN).
[0065] Comparative Example 2
[0066] A method for preparing graphitic carbon nitride (Nv / CN) with nitrogen vacancies includes: calcining graphitic carbon nitride (CN) at 620 °C for 4 h under an argon atmosphere (argon flow rate of 20 mL / min), cooling to room temperature, and manually grinding it into powder in an agate mortar for 10 min to obtain graphitic carbon nitride (Nv / CN) with nitrogen vacancies. The method for obtaining graphitic carbon nitride (CN) includes: holding dicyandiamide (powder) at 550 °C (heating rate to 550 °C is 2 °C / min) for 4 h, and cooling to room temperature to obtain graphitic carbon nitride (CN).
[0067] Comparative Example 3
[0068] A catalyst, which is the iron-doped graphitic carbon nitride (Fe / CN) prepared in step 1 of Example 3.
[0069] The morphology, crystal structure, and elemental distribution of the nitrogen-vacancy-bearing iron-doped graphitic carbon nitride catalyst prepared in Example 3 were characterized using transmission electron microscopy (TEM) and condenser aberration-corrected transmission electron microscopy (AC-TEM). The results are as follows: Figure 1 and Figure 2 As shown, where, Figure 1 Image a is a TEM image of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3. Figure 1 b is the aberration-corrected HAADF-STEM image of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3. Figure 2 The image shows the elemental mapping of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3.
[0070] Depend on Figure 1 As shown in b, the C and N-based graphitic carbon nitride support appears as a dark substrate. Fe atoms, with higher atomic numbers than C and N, exhibit discrete, separated bright spot signals in the image. No clustered bright spots corresponding to iron nanoparticles or metal clusters were observed in the image, indicating that iron species are uniformly dispersed on the graphitic carbon nitride support in the form of single-atom sites. Figure 2 It is known that the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 includes C, N and Fe elements, and Fe, C and N are uniformly distributed in the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3.
[0071] The sample was tested using an X-ray diffractometer to obtain... Figure 3 The X-ray diffraction patterns shown are for samples from one of the following: graphitic carbon nitride (CN) prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3. Figure 3 It can be seen that the diffraction peaks of the graphitic carbon nitride (CN) prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 all correspond well with the standard card (JCPDS card No. 87-1526) of graphitic carbon nitride (g-C3N4). Among them, no characteristic peaks related to Fe were found in the X-ray diffraction pattern of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3. This phenomenon is attributed to the fact that iron atoms are uniformly anchored and dispersed in the carbon nitride framework by relying on nitrogen vacancy sites. The iron species are highly dispersed in atomic form and have not agglomerated and crystallized. Therefore, there is no iron phase diffraction signal in the X-ray diffraction pattern.
[0072] Figure 4Fourier transform infrared spectra of the graphitic carbon nitride (CN) prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 1, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Examples 3-4. Figure 4 This indicates that the Fourier transform infrared spectra of Comparative Example 1, Comparative Example 3, Example 1, and Examples 3-4 are all within 810 cm⁻¹. -1 1200~1600 cm -1 The presence of characteristic absorption peaks indicates that doping with iron and creating nitrogen vacancies will not change the basic chemical framework of carbon nitride.
[0073] The sample was tested using a UV / Vis / NIR diffuse reflectance spectrometer to obtain... Figure 5 The UV-Vis diffuse reflectance spectra shown are used to evaluate the optical properties of the samples. The samples are one of the graphitic carbon nitride (CN) prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3. Figure 5 The results show that the absorption edge of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 is broadened from around 460 nm in pure graphitic carbon nitride to 550-600 nm after anchoring Fe single atoms, showing a significant red shift. The introduction of nitrogen vacancies in Example 3 can further enhance its light absorption capability.
[0074] The sample was tested using steady-state / transient fluorescence spectroscopy (PL) to obtain... Figure 6 The photoluminescence spectra shown are for one of the following samples: graphitic carbon nitride (CN) prepared in Comparative Example 1, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3. Figure 6 The results show that, compared with the graphitic carbon nitride (CN) of Comparative Example 1, the catalyst prepared in Comparative Example 3 and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 exhibited significant photoluminescence quenching (PL quenching). This phenomenon indicates that Fe single atoms and nitrogen vacancies can synergistically construct a fast charge transport channel, significantly improving the utilization efficiency of photogenerated carriers, reducing ineffective electron-hole recombination, and enabling more free photogenerated electrons and holes to migrate to the catalyst surface to participate in the catalytic reaction. Under the same illumination conditions, more active free radicals can be induced, thereby significantly improving the catalytic degradation efficiency of pollutants. This also corroborates the modification strategy of iron doping coupled with nitrogen vacancy construction, which is an effective way to optimize the charge separation efficiency of graphitic carbon nitride and improve its photocatalytic performance.
[0075] Test Example 1
[0076] Experiment 1: 5 mg of catalyst, 10 mg of PMS, and 50 mL of pollutant solution were placed in a 100 mL beaker to obtain a reaction solution. The reaction solution was subjected to photocatalytic reaction at 25 °C under xenon lamp irradiation and mechanical stirring at 450 r / min. 1 mL of the liquid was collected at the T-minute mark of the photocatalytic reaction as the test solution. The concentration of pollutants in the test solution was determined using ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS / MS). (A stock solution with a pollutant concentration of 1 mg / L was prepared by mixing the pollutant with deionized water. The stock solution was then diluted with deionized water to obtain pollutant concentrations of 0.01 mg / L, 0.05 mg / L, 0.1 mg / L, 0.2 mg / L, 0.5 mg / L, and 1 mg / L.) A standard solution of mg / L was used. Each standard solution was measured sequentially using UPLC-MS / MS, and the corresponding chromatographic peak area was collected. A standard curve was plotted with the pollutant concentration (mg / L) as the abscissa and the chromatographic peak area as the ordinate. The chromatographic peak area of the test solution was measured using UPLC-MS / MS, and the peak area of the test solution was substituted into the standard curve to obtain the concentration of the pollutant in the test solution, denoted as C. T min was one of 0 min, 0.5 min, 1 min, 2 min, 3 min, 4 min, and 5 min. The catalyst was one of the following: graphitic carbon nitride (CN) prepared in Comparative Example 1, graphitic carbon nitride with nitrogen vacancies (Nv / CN) prepared in Comparative Example 2, the catalyst prepared in Comparative Example 3, and iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Examples 1-4. The pollutant solution was a mixture of pollutant and water, the pollutant was 6PPD-Q, the initial concentration (C0) of the pollutant in the pollutant solution was 1 mg / L, and the pH of the pollutant solution was 7.0. The pollutant removal rate was calculated based on C and C0, and the pollutant removal rate = [(1-(C / C0)]*100%. The results of Experiment 1 are as follows: Figure 7 As shown.
[0077] Experiment 2:
[0078] Control group 1 ( Figure 8 The experimental conditions for the "Light" catalyst are basically the same as those for the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 in "Experiment 1". The only difference is that PMS was not added.
[0079] Control group 2 ( Figure 8 The experimental conditions for “PMS” are basically the same as those for the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 in “Experiment 1”. The only difference is that “the reaction solution is subjected to photocatalytic reaction under xenon lamp irradiation and mechanical stirring at 450 r / min” is replaced with “the reaction solution is subjected to catalytic reaction under mechanical stirring at 450 r / min”.
[0080] Experimental group 1 ( Figure 8 "Photocatalysis + PMS": The photocatalytic reaction was carried out using the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 of "Experiment 1", which was used as Experiment 1 (i.e., Experiment 1 is the result of "the catalyst is the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3" in Experiment 1).
[0081] The results of Experiment 2 are as follows Figure 8 As shown.
[0082] Experiment 3: Essentially the same as Experiment 1, except that the pollutant was tetracycline (TC). In Experiment 3, the catalyst was one of the following: graphitic carbon nitride (CN) prepared in Comparative Example 1, graphitic carbon nitride with nitrogen vacancies (Nv / CN) prepared in Comparative Example 2, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3; T min was one of 0 min, 2 min, 5 min, 7 min, 10 min, 15 min, and 20 min. The results of Experiment 3 are as follows: Figure 9 As shown.
[0083] Experiment 4: Essentially the same as Experiment 1, except that the contaminant was sulfamethoxazole (SMX). In Experiment 4, the catalyst was one of the following: graphitic carbon nitride (CN) prepared in Comparative Example 1, graphitic carbon nitride with nitrogen vacancies (Nv / CN) prepared in Comparative Example 2, the catalyst prepared in Comparative Example 3, and the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3; T min was one of 0 min, 2 min, 5 min, 7 min, 10 min, 15 min, and 20 min. The results of Experiment 4 are as follows: Figure 10 As shown.
[0084] Depend on Figure 7 , Figure 9 and Figure 10 It can be seen that among the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3, the graphitic carbon nitride (CN) prepared in Comparative Example 1, the graphitic carbon nitride (Nv / CN) with nitrogen vacancies prepared in Comparative Example 2, and the catalyst prepared in Comparative Example 3, the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 exhibits the best removal effect. The construction of doping with Fe single atoms and nitrogen vacancies can significantly improve the pollutant removal effect. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 shows excellent removal performance for tetracycline, sulfamethoxazole, and 6PPD-Q, and has good versatility and practical application potential. Figure 8It is known that, under the condition of adding a catalyst, relying solely on PMS or light treatment alone has limited effect on pollutant removal. PMS and light treatment can synergistically improve the pollutant removal effect.
[0085] As the Fe doping amount increases, the removal of contaminants (6PPD-Q) in the iron-doped graphitic carbon nitride catalysts with nitrogen vacancies prepared in Examples 1-4 first increases and then decreases.
[0086] Test Example 2
[0087] The stability and anti-interference ability of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 were further investigated through anti-interference testing. The anti-interference test included: placing 5 mg of catalyst, 10 mg of PMS, interfering substance, and 50 mL of contaminant solution (the same contaminant solution as in Experiment 1 of Test Example 1) into a 100 mL beaker to obtain a reaction solution. The reaction solution was subjected to photocatalytic reaction at 25 °C under xenon lamp irradiation and mechanical stirring at 450 r / min. At the 5th minute of the photocatalytic reaction, 1 mL of the liquid was taken as the test solution. The concentration of the contaminant in the test solution was obtained according to the method in Experiment 1 of Test Example 1, and denoted as C. The interfering substance was either a salt or humic acid (HA), with the salt being NaCl (Cl- released in the test solution). - As a coexisting ion), Na2SO4 (SO4 is released in the test solution). 2- As a coexisting ion), NaNO3 (NO3 is released into the test solution). - As a coexisting ion), Na2CO3 (CO3 is released into the test solution). 2- As a coexisting ion), NaHCO3 (HCO3 is released into the test solution). - (as coexisting ions) and Na2HPO4 (HPO4 is released free in the test solution). 2- As one of the coexisting ions. The concentration of the interfering substance in the reaction solution is AmM. A = 1, 5, or 10. The test results are as follows: Figure 11 As shown.
[0088] Depend on Figure 11 It can be seen that even with the introduction of interfering substances, the pollutant removal rate is still above 90%, and each interfering substance has no significant effect on the removal effect of 6PPD-Q.
[0089] Test Example 3
[0090] pH Effect Experiment: The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 was used as the catalyst for photocatalytic reaction. The experimental conditions were basically the same as those in Experiment 1 of Test Example 1, except that in Test Example 3, the pH of the pollutant solution was 3, 5, 7, 9, or 11, and the pH was adjusted by hydrochloric acid (HCl concentration of 0.1 mol / L) or sodium hydroxide aqueous solution (NaOH concentration of 0.1 mol / L). 1 mL of the liquid was taken as the test solution at the first minute of the photocatalytic reaction, and the pollutant removal rate at different pH values was obtained as follows: Figure 12 As shown.
[0091] Depend on Figure 12 It can be seen that, within the pH range of 3-11, the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 exhibits good removal efficiency for 6PPD-Q. Combined with... Figure 11 and Figure 12 It can be seen that iron-doped graphitic carbon nitride catalysts with nitrogen vacancies are minimally affected by common environmental matrices in real water bodies.
[0092] Test Example 4
[0093] 5 mg of catalyst (the catalyst being the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3) and 50 mL of contaminant solution (the same contaminant solution as in Experiment 1 of Test Example 1) were placed in a 100 mL beaker and mechanically stirred at 450 r / min for 30 min at 25 °C. 10 mg of PMS was added to obtain a composite solution, which was then mechanically stirred at 450 r / min for 5 min at 25 °C under xenon lamp irradiation. During these 5 min periods, 5 mL of liquid was collected at min 0, min 1, min 3, and min 5 as the detection solution. Inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the Fe at min 0, min 1, min 3, and min 5, respectively. 2+ Concentration, test results as follows Figure 13 As shown.
[0094] Depend on Figure 13 It can be seen that at the 5th minute of degradation, the Fe in the detection solution corresponding to the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 was [data missing]. 2+ The concentration was 0.28 mg / L, which is far lower than the 10 mg / L specified in the "Water Pollutant Discharge Standard for Iron and Steel Industry" (GB13456-2012). This indicates that the iron-doped graphite carbon nitride catalyst with nitrogen vacancies of the present invention has high structural stability and environmental friendliness.
[0095] Test Example 5
[0096] The mineralization ability of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 was further investigated.
[0097] 5 mg of catalyst, 10 mg of PMS, and 50 mL of pollutant solution (the same pollutant solution as in Experiment 1 of Test Example 1) were placed in a 100 mL beaker to obtain a reaction solution. The solution was mechanically stirred at 450 r / min for 30 min under xenon lamp irradiation at 25 ℃. During these 30 min periods, 5 mL of liquid was collected at each of the M min intervals (Mmin being 0 min, 10 min, 20 min, or 30 min), and the total organic carbon (TOC) value was measured using a total organic carbon analyzer. The TOC removal rate was then calculated using the formula: TOC removal rate = [1 - (TOC...] M / TOC0)]×100%, where TOC0 is the total organic carbon value measured at 0 min of reaction, TOC M The total organic carbon value was measured at reaction time M min. The catalyst was one of the following: the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3; the graphitic carbon nitride (CN) prepared in Comparative Example 1; the graphitic carbon nitride with nitrogen vacancies (Nv / CN) prepared in Comparative Example 2; and the catalyst prepared in Comparative Example 3. Results are as follows: Figure 14 As shown.
[0098] Depend on Figure 14 It can be seen that the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 achieved a TOC removal rate of nearly 50% at 30 min; while the catalyst prepared in Comparative Example 3 achieved a TOC removal rate of less than 10% at the same time. This indicates that the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies of the present invention can effectively mineralize 6PPD-Q and has good mineralization ability.
[0099] Test Example 6
[0100] Quenching Experiment: This experiment is essentially the same as "Experiment 1" in Test Example 1, except that the reaction solution is different. The method for obtaining the reaction solution in the quenching experiment involves placing 5 mg of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3, 10 mg of PMS, a quencher, and 50 mL of contaminant solution into a 100 mL beaker to obtain the reaction solution (the concentration of the quencher in the reaction solution after adding the quencher is 100 mmol / L). The quencher is L-histidine (L-His) (which quenches singlet oxygen). 1 O2), methanol (MeOH) (quenching sulfate free radicals (SO4) ·- ) and tert-butanol (TBA) (quenches hydroxyl radicals (·OH)), superoxide dismutase (SOD) (quenches superoxide radicals (O2)). ·-)) and disodium ethylenediaminetetraacetate (EDTA-2Na) (quenching holes (h + One of them.
[0101] Quenching control experiment: The photocatalytic reaction was carried out using the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 of Experiment 1 of Test Example 1 (i.e., the quenching control experiment was the result of Experiment 1 with "the catalyst being the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3", without the addition of quencher).
[0102] Quenching experiment and quenching control experiment ( Figure 15 The results of "Example 3" are as follows: Figure 15 As shown. By Figure 15 It can be seen that, compared with the quenching control experiment, the degradation effect of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 on 6PPD-Q only showed a slight decrease after the addition of MeOH and TBA, indicating that SO42- ·- ·OH is not the dominant active species in this reaction system; the addition of SOD and EDTA-2Na significantly inhibited the degradation effect, indicating that O2 ·- with h + It participates in the degradation reaction and is an important auxiliary active species, but its contribution is lower than that of singlet oxygen; however, the degradation effect of 6PPD-Q is significantly inhibited after the addition of L-His. 1 O2 is the dominant active species in the activation of PMS during the degradation of 6PPD-Q by the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3.
[0103] The above results clarify the reaction pathway of this catalytic system: in the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies, nitrogen vacancies and Fe single atoms synergistically activate PMS, mainly through a non-radical pathway. 1 O2 enables the efficient degradation of 6PPD-Q, providing direct experimental evidence for the mechanism of action of the catalyst.
[0104] Test Example 7
[0105] capture 1 O2 Experiment: 5 mg of catalyst, 10 mg of PMS, the first trapping agent, and 50 mL of pollutant solution were placed in a 100 mL beaker to obtain the first mixture. The mixture was mechanically stirred at 450 r / min for 5 min under xenon lamp irradiation at 25 ℃. Samples were taken, and the concentration of O2 in the samples was determined using a Bruker A200 electron paramagnetic resonance (EPR) spectrometer. 1The EPR response signal intensity of O2. The catalyst was one of the following: the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3; the graphitic carbon nitride (CN) prepared in Comparative Example 1; the graphitic carbon nitride (Nv / CN) with nitrogen vacancies prepared in Comparative Example 2; and the catalyst prepared in Comparative Example 3. The first trapping agent was 2,2,6,6-tetramethylpiperidine (TEMP), and the concentration of the first trapping agent in the first mixture was 30 μmol / L. The test results are as follows: Figure 16 As shown.
[0106] Depend on Figure 16 It can be seen that TEMP captures 1 O2 generates a characteristic triple isotropic EPR signal; only a very weak EPR signal is detected in the corresponding electron paramagnetic resonance spectrum of Comparative Example 1. 1 The O2 characteristic peak indicates extremely low singlet oxygen content. The characteristic triplet isopeak signal intensity of Comparative Example 2 (Nv / CN) with introduced nitrogen vacancies is slightly increased compared to Comparative Example 1. The characteristic triplet isopeak signal intensity of Comparative Example 3 is further enhanced. The iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 exhibits the highest characteristic triplet isopeak signal intensity. This indicates that nitrogen vacancies are generated by activating PMS. 1 The effective defect sites of O2, iron doping and nitrogen vacancies have a synergistic effect, and their coexistence can significantly optimize the separation efficiency of photogenerated carriers and significantly improve the activation efficiency of PMS. 1 O2 production.
[0107] capture 1 O2 control experiment:
[0108] First control group ( Figure 17 "Light" in the middle: and "capture" 1 The experimental conditions for the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 in the "O2 Experiment" were basically the same, except that PMS was not added.
[0109] Second control group ( Figure 17 "PMS" in Chinese: (and "capture") 1 The experimental conditions for the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 in the "O2 Experiment" were basically the same, except that "mechanical stirring at 450 r / min for 5 min under xenon lamp irradiation at 25 ℃" was replaced with "mechanical stirring at 450 r / min for 5 min at 25 ℃".
[0110] Will capture 1 In the O2 experiment, the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 was used as the catalyst. Figure 17Results and capture of "light + PMS" 1 The results of the O2 control experiment were plotted on Figure 17 .
[0111] Depend on Figure 17 It can be seen that only light ( Figure 17 (in the middle of the light) almost no 1 O2 characteristic EPR signal; only PMS added and stirred in the dark ( Figure 17 Weakness occurs when "PMS" is in use. 1 O2 characteristic peak; coexistence of illumination and PMS ( Figure 17 "Light + PMS" 1 The O2 characteristic EPR signal intensity increased significantly, indicating that it is difficult to generate large quantities using a single illumination or a single PMS system. 1 O2 and light-induced PMS activation are the main factors contributing to the large-scale production of this system. 1 A necessary condition for O2.
[0112] Hole trapping experiment: 5 mg of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3, 10 mg of PMS, a second trapping agent, and 50 mL of contaminant solution were placed in a 100 mL beaker to obtain a second mixture. The mixture was mechanically stirred at 450 r / min for 10 min under xenon lamp irradiation at 25 °C. During these 10 min periods, 1 mL samples were taken at min 0, min 5, and min 10, and the number of holes (h) in the samples was detected using a Bruker A200 electron paramagnetic resonance (EPR) spectrometer. + The EPR response signal intensity of the mixture was measured, where the second trapping agent was 2,2,6,6-tetramethylpiperidine-1-oxygen radical (TEMPO), and the concentration of the second trapping agent in the second mixture was 30 μmol / L. The test results are as follows: Figure 18 As shown.
[0113] Depend on Figure 18 It can be seen that TEMPO can specifically capture holes (h) in the system. + The photocatalyst generates a characteristic triple isopeaker, with the strongest EPR signal corresponding to holes at 0 min. As the irradiation time increases to 5 min and 10 min, the EPR signal intensity corresponding to holes gradually decreases. This indicates that the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies can continuously generate holes (h) under irradiation. + Furthermore, the intensity of the characteristic triple iso-peak EPR signal gradually decreases with increasing reaction time. This is because of holes (h + Iron-doped graphitic carbon nitride catalysts with nitrogen vacancies adhere to the surface of the catalyst and participate in the reaction, confirming that the holes (h) +() is one of the important active oxide species for the degradation of pollutants in this catalytic system.
[0114] Test Example 8
[0115] The formation of nitrogen vacancies in the catalyst was characterized using electron paramagnetic resonance (EPR) spectroscopy. At room temperature (25 °C), the catalyst (dry solid powder) was placed in the EPR sample tube of the EPR spectrometer for testing. A central magnetic field was set during the test, and the scanning field covered the range of g = 1.96–2.04. The catalyst was one of the following: the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3; the graphitic carbon nitride (CN) prepared in Comparative Example 1; the graphitic carbon nitride (Nv / CN) with nitrogen vacancies prepared in Comparative Example 2; and the catalyst prepared in Comparative Example 3. The results are as follows: Figure 19 As shown.
[0116] Depend on Figure 19 It can be seen that the graphitic carbon nitride (CN) prepared in Comparative Example 1 has no obvious characteristic signal at the position of g≈2.0032; the graphitic carbon nitride (Nv / CN) with nitrogen vacancies prepared in Comparative Example 2 shows a weak nitrogen vacancy characteristic signal at the position of g≈2.0032; the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies prepared in Example 3 shows a significantly enhanced EPR characteristic signal peak at the position of g≈2.0032, which is a typical characteristic peak of the paramagnetic center of nitrogen vacancy in the graphitic carbon nitride framework.
[0117] The above results show that the present invention successfully constructs nitrogen vacancies through a two-calcination process. The introduction of nitrogen vacancies provides abundant defective active sites for the catalyst, which, together with iron single atoms, synergistically regulate the electronic structure and carrier separation efficiency, thereby improving the degradation effect of 6PPD-Q.
[0118] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A catalyst, characterized in that, It is iron-doped graphitic carbon nitride, and graphitic carbon nitride contains nitrogen vacancies.
2. A method for preparing an iron-doped graphitic carbon nitride catalyst with nitrogen vacancies, characterized in that, Includes the following steps: Step 1: Mix dicyandiamide, water and iron source, stir at 80~100℃ until water evaporates completely, grind, keep the ground powder at 540~560℃ for 3.5~4h, cool to room temperature to obtain iron-doped graphitic carbon nitride, wherein the mass fraction of dicyandiamide to the molar fraction of iron in the iron source is 2:(0.25~1), the mass fraction is in g, and the molar fraction is in mmol; Step 2: Under a nitrogen or inert gas atmosphere, iron-doped graphitic carbon nitride is heated at 600~620℃ for 3.5~4 h and then cooled to room temperature to obtain an iron-doped graphitic carbon nitride catalyst with nitrogen vacancies.
3. The preparation method according to claim 2, characterized in that, In step 1, the ratio of the mass fraction of dicyandiamide to the volume fraction of water is 2:(20~30), where the mass fraction is in g and the volume fraction is in mL.
4. The preparation method according to claim 2, characterized in that, In step 1, the iron source is ferric chloride hexahydrate.
5. The application of the iron-doped graphitic carbon nitride catalyst with nitrogen vacancies as described in claim 1 in the degradation of pollutants.
6. The application according to claim 5, characterized in that, The contaminant is at least one of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine quinone, tetracycline, and sulfamethoxazole.
7. The application according to claim 5, characterized in that, Iron-doped graphitic carbon nitride catalysts with nitrogen vacancies activate PMS under light irradiation to produce singlet oxygen.